Kefektivitas Pengunaan Media Pembelajaran dalam Meningkatkan Minat Belajar Kognitif Siswa Sekolah Dasar Kelas III SDN Sindang Panon 2 - Zahranisa, Anida; Marlina, Nana; Zuliani, Rizki (Lembaga Yasin AlSys, 2023)
The effectiveness of the use of learning media is an effort to achieve the targets that have been set according to the needs, plans, using data, facilities, and available time to obtain maximum results both qualitatively. Learning media is a tool that can help the teaching and learning process. The purpose of this writer is to determine the effectiveness of the equipped learning media. with learning models. The method used in this study using observation techniques. Conclusion learning media and learning models are needed in the teaching and learning process because the presence of media and the models used can improve student learning outcomes. This study aims to determine: 1) student learning outcomes by using instructional media to increase students' cognitive learning interest. 2) student learning outcomes by using learning media can reach the level of students' cognitive learning interest. 3) is there a difference in learning outcomes using learning media and media modules on student competence. This type of research is a qualitative approach. The research was conducted from January to June. Methods of data collection using observation. Validity and Reliability using learning media. Data analysis techniques by making learning media directly. The results showed that: 1) Student learning outcomes for class V by using instructional media can improve students' cognitive learning. 2) Student learning outcomes in class V by using instructional media can be said to increase. This is evident in the use of module learning media showing significant differential power, namely calculated 2.120> 1.880 tabled at a significant level of 5%. Thus it can be concluded that the hypothesis that reads